Themostable alkaline serine protease from thermophilic bacillus species. - Norazila Yusoff; Noor Azlina Ibrahim (International Science Congress Association, 2012)
Screening and isolation of proteolytic bacteria were carried out from water samples of Lojing hot spring (Kelantan, Malaysia). Based on the qualitative screening on Skim Milk Agar (SMA), two isolates showed positive results by forming clearing zones around the colonies on SMA. The isolates were identified as Bacillus subtilis 50a and B. licheniformis 50b on the basis of the 16s rRNA gene sequencing. The effect of temperature, pH and inhibitors on enzymes activity and stability were investigated. The crude proteases for both isolates displayed maximal activity at 70˚C and showed characteristic pH optima at pH 9.0. Enzyme activity was totally inhibited by phenylmethyl sulphonyl fluoride (PMSF), suggested that the protease from B. subtilis 50a and B. licehniformis 50b belong to the family of serine protease. The thermostability profile exhibited the protease from B. subtilis 50a was very stable at 50˚C (maintain 100% relative activity) and the protease activity retained 89% of its original activity after heat treatment at 60˚C for 30 min. Meanwhile, protease activity for B. licheniformis 50b retained 96 and 72% of the original activity after heat treatment at 50 and 60 ˚C, respectively. Considering their promising properties, B. subtillis %0a and B. licheniformis 50b could be a potential sources of enzyme for industrial applications.